HUMAN RESOURCE CAPACITY IMPROVEMENT OF CANTEEN VENDORS AT SMPN 1 BANGKALAN - dinii setiarsih; Eka Firdianita Fujiatus Sholiha; Vera Ardilla Rimba Kharisma; Nandita Cahyani Putri (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2026)
School canteens play an important role in providing safe, nutritious, healthy, and halal food for students. SMPN 1 Bangkalan still faces obstacles in the low capacity of canteen vendors regarding balanced nutrition, food safety, and sanitation hygiene. This activity aims to increase the knowledge of canteen vendors about healthy canteens and food safety. The target of the activity is all canteen vendors at SMPN 1 Bangkalan. The activity method includes socialization of canteen vendors and education on healthy canteens and food safety. Educational media use modules, presentations, and flyers. Evaluation is carried out with pre-tests and post-tests. The results of the activity show an increase in participants' knowledge about healthy canteens and food safety, especially in choosing healthy snacks, storing food ingredients, and maintaining cleanliness. This program can be concluded as effective in encouraging the implementation of sustainable healthy canteen standards at SMPN 1 Bangkalan.